# PSAT Math : Exponents

## Example Questions

← Previous 1 3 4 5 6 7 8 9 14 15

### Example Question #1 : How To Add Exponents

If a2 = 35 and b2 = 52 then a4 + b6 = ?

Possible Answers:

150,000

141,833

140,608

522

3929

Correct answer:

141,833

Explanation:

a4 = a2 * a2  and  b6= b2 * b* b2

Therefore a4 + b6 = 35 * 35 + 52 * 52 * 52 = 1,225 + 140,608 = 141,833

### Example Question #91 : Exponents

If , what is the value of ?

Possible Answers:    Correct answer: Explanation:

Since we have two ’s in we will need to combine the two terms.

For this can be rewritten as So we have .

Or Divide this by  Thus or *Hint: If you are really unsure, you could have plugged in the numbers and found that the first choice worked in the equation.

### Example Question #2 : How To Add Exponents

Solve for x.

2+ 2x+1 = 72

Possible Answers:

7

6

3

4

5

Correct answer:

5

Explanation:

The answer is 5.

8 + 2x+1 = 72

2x+1 = 64

2x+1 = 26

x + 1 = 6

x = 5

### Example Question #3 : How To Add Exponents

Which of the following is eqivalent to 5b – 5(b–1) – 5(b–1) – 5(b–1) – 5(b–1) – 5(b–1) , where b is a constant?

Possible Answers:

1

5

1/5

5b–1

0

Correct answer:

0

Explanation:

We want to simplify 5b – 5(b–1) – 5(b–1) – 5(b–1) – 5(b–1) – 5(b–1) .

Notice that we can collect the –5(b–1) terms, because they are like terms. There are 5 of them, so that means we can write –5(b–1) – 5(b–1) – 5(b–1) – 5(b–1) – 5(b–1) as (–5(b–1))5.

To summarize thus far:

5b – 5(b–1) – 5(b–1) – 5(b–1) – 5(b–1) – 5(b–1) = 5b +(–5(b–1))5

It's important to interpret –5(b–1) as (–1)5(b–1) because the –1 is not raised to the (b – 1) power along with the five. This means we can rewrite the expression as follows:

5b +(–5(b–1))5 = 5b + (–1)(5(b–1))(5) = 5b – (5(b–1))(5)

Notice that 5(b–1) and 5 both have a base of 5. This means we can apply the property of exponents which states that, in general, abac = ab+c. We can rewrite 5 as 51 and then apply this rule.

5b – (5(b–1))(5) = 5b – (5(b–1))(51) = 5b – 5(b–1+1)

Now, we will simplify the exponent b – 1 + 1 and write it as simply b.

5b – 5(b–1+1) = 5b – 5b = 0

The answer is 0.

### Example Question #4 : How To Add Exponents

If , then what does equal?

Possible Answers:     Correct answer: Explanation: ### Example Question #5 : How To Add Exponents

Simplify.  All exponents must be positive. Possible Answers:     Correct answer: Explanation:

Step 1: Step 2: Step 3: (Correct Answer): ### Example Question #6 : How To Add Exponents

Simplify.  All exponents must be positive. Possible Answers:     Correct answer: Explanation:

Step 1: Step 2: Step 3: ### Example Question #1 : Exponents Answer must be with positive exponents only.

Possible Answers:     Correct answer: Explanation:

Step 1: Step 2: The above is equal to ### Example Question #9 : Exponents

Evaluate: Possible Answers:     Correct answer: Explanation:   ### Example Question #10 : Exponents

Simplify: Possible Answers:     Correct answer: Explanation: Similarly So ← Previous 1 3 4 5 6 7 8 9 14 15

### All PSAT Math Resources 